Simulate air flow & heat transfer for different building by using computational fluid dynamics (CFD) modelling - Kwek, Nicole Xiao Qian (Nanyang Technological University, 2021)
This report aims to help users understand the importance of Computational Fluid Dynamic (CFD) as it helps to reduce material waste and reduce the time taken used for each experiments if it was done in the traditional method. Firstly, this report attempt to fill up research gaps on using the mixed ventilation system which is known as hybrid ventilation system where natural and mechanical driving forces is used and how it will improve ventilation as compared to using natural ventilation system. Next, it is to check if the location of the outlets (fully opened windows or exhaust fans) affect the ventilation in the case study where the inlets are normally the same across all the scenarios unless otherwise stated.